The role of heat shock proteins in Behcet's disease - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2003)
Heat shock proteins (HSP) are highly conserved molecules with scavenger activity that are involved in the correct folding of newly synthesized proteins. Increased T and B cell activity against 60165 kD HSP is observed in different ethnic populations in Behcet's disease (BD) with both alphabeta and gammadelta T cell responses. Although the specificity of these responses is not clear, animal models of uveitis treated with either subcutaneous and oral HSP-derived peptides suggest a significant role of HSPs in the immunopathogenesis of BD. Recent developments in the innate immune system with the description of toll-like receptors (TLR) and HSP60 as a ligand for TLR-2 and TLR-4 suggest also the role of HSP60 as an endogenous danger signal to the immune system with rapid inflammatory cytokine release and the enhancement of adaptive Th1-type responses. Activation of both innate and adaptive responses with HSPs also fit well into the clinical spectrum of BD with both early, limited responses (recurrent ulcers, pathergy, etc.) and chronic lesions (posterior uveitis, thrombosis, neuro-BD, etc.).
Keywords: Behcet's disease; heatshock proteins; immune pathogenesis; DELTA T-CELLS; ALPHA-B-CRYSTALLIN; IMMUNE-RESPONSE; STREPTOCOCCUS-SANGUIS; DENDRITIC CELLS; GAMMA; EXPRESSION; RECEPTOR; ANTIGENS; ACTIVATE